2018
DOI: 10.1021/acs.jchemed.7b00764
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Curriculum for a Structure, Reactivity, and Quantitation Sequence in Chemistry

Abstract: A novel laboratory curriculum is presented, developed around some common tasks of a laboratory researcher in chemistry: purification, synthesis, and measurement. The capstone of the sequence is an integrated laboratory, leading to a more independent research experience. Students who have completed this laboratory curriculum appear to perform comparably to previous students who completed a more traditional curriculum, based on their handling of American Chemical Society Exam questions and career placement. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Over past few years, we have reported the development of our new curriculum, the introductory course, three courses in the reactivity sequence, and our laboratory curriculum . In this paper, we report the development, implementation, and assessment of our first course in the quantitation area (Chem 255).…”
Section: Our New Chemistry Curriculum: Structure Reactivity and Quant...mentioning
confidence: 99%
“…Over past few years, we have reported the development of our new curriculum, the introductory course, three courses in the reactivity sequence, and our laboratory curriculum . In this paper, we report the development, implementation, and assessment of our first course in the quantitation area (Chem 255).…”
Section: Our New Chemistry Curriculum: Structure Reactivity and Quant...mentioning
confidence: 99%
“…Their stated goal is to present a “more unified view of how traditional subdisciplines of chemistry relate to each other.” The foundation level consists of six courses, with each course tying to the three larger themes. These courses prepare students to take a variety of upper-level, special topics courses based on student career interests and choice of major. CSB/SJU has also implemented a redesigned laboratory curriculum independent of their lecture courses, with themes of purification, synthesis, and measurement …”
Section: Previous Reform Efforts: Literature Reviewmentioning
confidence: 99%
“…CSB/SJU has also implemented a redesigned laboratory curriculum independent of their lecture courses, with themes of purification, synthesis, and measurement. 59 ■ TAKING THE LEAP: DESIGN AND PROCESS In the design of Chemistry Unbound, we thoroughly examined the reform work of other institutions and drew heavily on the ideas and foundational work in curricular reform of these programs. However, we ultimately found that these reforms only addressed a subset of the goals outlined above.…”
Section: Reform Goalsmentioning
confidence: 99%
“…8 Liquid−liquid extraction (LLE) is challenging for students to learn, even at the graduate and postgraduate level, 9 because it requires an understanding of how solution pH impacts chemical structure, and how these structural changes and solvent polarity impact solubility and partition equilibria. Despite these challenges, many experiments in this Journal invoke LLE, either as part of a reaction workup, 10 or to extract compounds from water, 11 artificial mixtures, 12 drug formulations, 13 lotions, 14 tea, 15 plants, 15,16 essential oils, 17,18 food, 19,20 and beverages. 21,22 Another common LLE experiment involves separating colored dyes from mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liquid–liquid extraction (LLE) is challenging for students to learn, even at the graduate and postgraduate level, because it requires an understanding of how solution pH impacts chemical structure, and how these structural changes and solvent polarity impact solubility and partition equilibria. Despite these challenges, many experiments in this Journal invoke LLE, either as part of a reaction workup, or to extract compounds from water, artificial mixtures, drug formulations, lotions, tea, plants, , essential oils, , food, , and beverages. , Another common LLE experiment involves separating colored dyes from mixtures. Most of these experiments focus on students executing the technique by providing recipes for them to follow. Several experiments go farther, for example, by having students examine the relationship between pH and solubility. ,, Some inquiry-based LLE experiments have been reported, which usually involve students designing an LLE to isolate a specific compound. ,, For example, Pontrello’s students designed an LLE procedure that was peer-reviewed and then given to another student for testing .…”
Section: Introductionmentioning
confidence: 99%